Designing an Intuitive User Experience: SATURI’s UI/UX Approach to Public Service Access in Indonesia - Kurnia Prima Putra; Mukhlishah Afdhaliyah; Putri Angraeni Badar; Putri Angraeni (Jurusan Teknik Informatika dan Komputer, 2025)
This study explores the development and implementation of SATURI (Satu Akses Terintegrasi Rakyat Indonesia), a comprehensive digital platform designed to centralize public service access for Indonesian citizens. Indonesia faces significant challenges in adopting digital public services, particularly due to low digital literacy, fragmented service platforms, and issues of usability. This study follows the Design Thinking methodology, which includes Empathy, Define, Ideate, Prototype, and Test phases, to develop and refine SATURI. The Empathy phase revealed that citizens, especially in rural areas, encounter difficulty accessing and navigating digital public services. Through user-centered design, the platform integrates multiple government services, such as applying for ID cards, licenses, and tax payments, into a single interface, with features like automated data entry and geolocation services. The Ideate phase focused on developing innovative solutions to the challenges identified, while the Prototype and Test phases involved extensive usability testing and focus group discussions. Feedback led to improvements in usability, accessibility, and user satisfaction, particularly through the introduction of interactive tutorials and live chat support. The results suggest that SATURI could significantly enhance the efficiency and accessibility of public services in Indonesia, offering a more inclusive and user-friendly solution for citizens, especially those with low digital literacy. The study concludes with recommendations for expanding service integrations, improving mobile accessibility, and incorporating continuous user feedback to ensure that SATURI remains adaptable and effective for all users.